1975
DOI: 10.1037/h0076125
|View full text |Cite
|
Sign up to set email alerts
|

Language delay and associated mother-child interactions.

Abstract: The home environments and mother-child interactions of a language-delayed group and a matched control group of normal preschool children were assessed using the Caldwell Inventory of Home Stimulation. Twenty language-delayed children were defined by a discrepancy between their Stanford-Binet, language-based, IQ score and their Leiter, non-language-based, IQ score, and by a language evaluation. Children in both groups were distributed across all socioeconomic strata. The languagedelayed group had significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
0
3

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(34 citation statements)
references
References 29 publications
4
27
0
3
Order By: Relevance
“…For example, some researchers (Cramblit & Siegel 1977, Lasky & Klopp 1982, Whitehurst, Fischel, Lonigan, Valdez-Menchaca, DeBaryshe & Caulfield 1988 have observed few differences between the interactions of parents with language-normal children versus language-impaired children, or have argued that the greater number of maternal initiations observed with language-impaired children are an appropriate and responsive adaptation to the child's linguistic delays (Conti-Ramsden & Friel-Patti, 1983). In contrast, others have observed mothers of language-impaired children to be more directive (Cross 1981, Schodorf & Edwards 1983, less responsive (Wulbert, Inglis, Kriegsman & Mills 1975), to engage in less speech related to the child's activity (Petersen & Sherrod 1982) and to the child's speech (Cross 1981, Schodorf & Edwards 1983, and to speak more utterances with non-specific references (Harris, Jones, Brookes & Grant 1986, Petersen & Sherrod 1982, Wulbert, et al 1975. Although some of these maternal behaviours may be construed as resulting from the language-impaired child making fewer initiations (Conti-Ramsden & FrielPatti 1983) and more inappropriate answers to requests (Brinton & Fujiki 1982), there is nonetheless the lingering suggestion that parental behaviour may become maladaptive in response to the child (Cross, Nienhuys & Kirkman 1985) and contribute to the maintenance of language-impairment (Schodorf & Edwards 1983).…”
mentioning
confidence: 81%
“…For example, some researchers (Cramblit & Siegel 1977, Lasky & Klopp 1982, Whitehurst, Fischel, Lonigan, Valdez-Menchaca, DeBaryshe & Caulfield 1988 have observed few differences between the interactions of parents with language-normal children versus language-impaired children, or have argued that the greater number of maternal initiations observed with language-impaired children are an appropriate and responsive adaptation to the child's linguistic delays (Conti-Ramsden & Friel-Patti, 1983). In contrast, others have observed mothers of language-impaired children to be more directive (Cross 1981, Schodorf & Edwards 1983, less responsive (Wulbert, Inglis, Kriegsman & Mills 1975), to engage in less speech related to the child's activity (Petersen & Sherrod 1982) and to the child's speech (Cross 1981, Schodorf & Edwards 1983, and to speak more utterances with non-specific references (Harris, Jones, Brookes & Grant 1986, Petersen & Sherrod 1982, Wulbert, et al 1975. Although some of these maternal behaviours may be construed as resulting from the language-impaired child making fewer initiations (Conti-Ramsden & FrielPatti 1983) and more inappropriate answers to requests (Brinton & Fujiki 1982), there is nonetheless the lingering suggestion that parental behaviour may become maladaptive in response to the child (Cross, Nienhuys & Kirkman 1985) and contribute to the maintenance of language-impairment (Schodorf & Edwards 1983).…”
mentioning
confidence: 81%
“…They found that only 20% of mothers' utterances were semantically related to the children's speech and that mothers ignored their children's verbal and/or nonverbal initiations approximately 88% of the time. It has also been reported that mothers of 2-to 5-year-olds with language delays are more critical, controlling, and punitive, as well as less interactive, than mothers of normally developing peers (Wulbert, Inglis, Kriegsmann, & Mills, 1975). Additional evidence along this line comes from Rocissano and Yatchmink (1983), who found that prematurely born toddlers whose mothers were more synchronous during play had better language skills than those toddlers whose mothers were more controlling and asynchronous.…”
mentioning
confidence: 91%
“…Parental factors important for child speech development are: the number of words (Hart 1991, Huttenlocher, Haight, Bryk, Seltzer & Lyons 1991, Snow 1984; contingent responsiveness (Haugen & McIntire 1972, Poulson 1983; joint attention (Harris, Jones & Grant 1984/85, Ninio 1992, Tomasello & Todd 1983; and several functions of adult speech to children (McDonald & Pien 1982, Snow 1984. The functions of speech related to later word production and vocabulary are: labelling and describing toys with which the child is currently playing (Harris et al 1984/85, Nelson 1973); positive affective speech (Wulbert, Inglis, Kriegsman & Mills 1975); and suggestions or requests by the mother to recruit infant activity (Nelson 1973). Functions of adult speech to children negatively related to later language production are prohibitions (Bee, VanEgeren, Streissguth, Nyman & Leckie 1969) and commands directing the child what to do (McDonald & Pien 1982, Pratt, Kerig, Cowan & Cowan 1992.…”
mentioning
confidence: 99%